2022
DOI: 10.1186/s41936-022-00278-7
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of African catfish and Nile tilapia briefly exposed to complex pesticide mixtures

Abstract: Background Pulse exposures are the consequences of the intermittent release of pollutants in the environment. Brief exposure of aquatic organisms to high concentrations of pesticides simultaneously occurs, particularly in small watercourses during high flows. The effects of pulse exposure often include effects occurring during and after the exposure. Despite this, routine toxicity tests procedures often ignore brief exposure scenarios and the role of time in toxicity. We conducted a pulse toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…2, a significant maximum bioflocs growth and surplus likely occurred on Day 21. Since the catfish was more endurance than the tilapia, this statement was in line with the research by Kanu et al [29], which found that catfish had a significantly higher survival probability than tilapia, so the surplus bioflocs should be more than 50 mg L −1 . Therefore, surplus bioflocs should be harvested.…”
Section: Bioflocs Performance In Reducing Nitrogenous Compoundsupporting
confidence: 87%
“…2, a significant maximum bioflocs growth and surplus likely occurred on Day 21. Since the catfish was more endurance than the tilapia, this statement was in line with the research by Kanu et al [29], which found that catfish had a significantly higher survival probability than tilapia, so the surplus bioflocs should be more than 50 mg L −1 . Therefore, surplus bioflocs should be harvested.…”
Section: Bioflocs Performance In Reducing Nitrogenous Compoundsupporting
confidence: 87%
“…2006; Bundschuh et al 2013;Kanu et al 2022). Therefore, to improve the extrapolation of laboratory results to natural ecosystems the inclusion of post-exposure periods in experimental setups is a relevant issue in ecotoxicology.…”
mentioning
confidence: 99%
“…Among toxicants, cadmium has been amply studied in ecotoxicology (Wright and Welbourn 1994;Irfan et al In natural ecosystems, the exposure of animals to pollution is not always chronic. Some toxicants can be in aquatic ecosystems during a short period, from a few hours to a few days (Handy 1994;Brent and Herricks 1998;Bundschuh et al 2013;Zhao and Newman 2006;Kanu et al 2022). Therefore, animals may face toxicants for a brief period and subsequently they could recover or not during the post-exposure period, which depends on the chemical compound, duration of the exposure and concentration of the toxicant (Zhao and Newman 2006;Hoang et al 2007;Alonso and Camargo 2009;Lahman and Moore 2015;Kanu et al 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation